2015
DOI: 10.1007/s10926-015-9583-4
|View full text |Cite
|
Sign up to set email alerts
|

Manager Experiences with the Return to Work Process in a Large, Publically Funded, Hospital Setting: Walking a Fine Line

Abstract: Although it is not their legislative responsibility, Danish managers play a key role in the RTW process. As has been observed in other contexts, Danish supervisors struggle to balance considerations for the returning worker with those of their teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
(70 reference statements)
4
24
0
Order By: Relevance
“…Moreover, similar to an earlier study by Stochkendahl et al, [15] this research found that a reliance on "may rules" does not mean that no actions are taken in Denmark. In almost half of the cases, supervisors took the responsibility to draw up a RTW plan, while Danish labor agreements ensured that wages are paid after the mandatory wage payment period of 30 days (to four to nine weeks for blue-collar workers and to one year for white-collar workers).…”
Section: "Must Rules" Versus "May Rules"supporting
confidence: 86%
See 3 more Smart Citations
“…Moreover, similar to an earlier study by Stochkendahl et al, [15] this research found that a reliance on "may rules" does not mean that no actions are taken in Denmark. In almost half of the cases, supervisors took the responsibility to draw up a RTW plan, while Danish labor agreements ensured that wages are paid after the mandatory wage payment period of 30 days (to four to nine weeks for blue-collar workers and to one year for white-collar workers).…”
Section: "Must Rules" Versus "May Rules"supporting
confidence: 86%
“…Workplace actors in both countries have obtained a statutory role in activating sicklisted employees to RTW early, albeit to a different extent. Legislation in the Netherlands stipulates that the RTW process is the shared responsibility of employers and employees; by contrast, since legislation in Denmark places the responsibility to initiate the RTW process with municipalities, less policy initiatives are focused on workplace actors, [15,31] who are the focus of this study. As shown in Table 1, the Dutch RTW legislation for workplaces is characterized by extensive, obligatory "must rules" coupled with sanctions, [27] whereas noncompulsory "may rules" (without sanctions) are characteristic of the Danish legislation.…”
Section: Research Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Supervisors play a key role in the job accommodation process [12]. Supervisors may be asked by their employer to interpret medical restrictions, document job demands, create modified duty positions, or temper production demands.…”
Section: Introductionmentioning
confidence: 99%